Design and Development of the Moving Score Virtual Reality Game as a Game Programmer - Maghribi, Muhammad Ridho; Geovanne Farell; Sheanny Ocmi Sakti; Wiki Lofandri (The Future of Education Journal, 2025)
The development of Virtual Reality (VR) technology opens up new opportunities to create exciting gameplay experiences while encouraging players to be more physically active. This study aims to design a VR-based game called Moving Score, focusing on the development of motion-based interaction systems and the implementation of responsive game mechanics. The game was developed using Unity and the XR Interaction Toolkit, featuring various elements such as a dynamic scoring system, visual and audio feedback, and real-time motion detection. The method used is prototyping, starting from needs identification, prototype development, to testing and iteration. The final results show that the game successfully delivers intuitive interaction, provides effective feedback, and enhances user engagement in a virtual environment. Moving Score not only offers entertainment but also holds potential as an educational medium that supports users' physical activity and movement coordination.